To be or not to be a case of heparin resistance - Jibran Durrani; Faizan Malik; Naveed Ali; Syed Imran Mustafa Jafri (Greater Baltimore Medical Center, 2018)
Heparin resistance can be defined as high doses of unfractionated heparin (UFH), greater than 35,000 IU/day, required to raise the activated partial thromboplastin time (aPTT) and activated coagulation time (ACT) to within therapeutically desired ranges or the impossibility of doing so. The most common pathology responsible is the deficiency of anti-thrombin III (ATIII) deficiency. Other clinically relevant conditions that can present with heparin resistance are congenital deficiencies; use of high doses of heparin during extracorporeal circulation, use of asparaginase therapy and disseminated intravascular coagulation (DIC). Most of these conditions effect the ATIII levels. Patients are typically identified in an acute phase, when determination of the cause of resistance is challenging. We present a case where a patient presented with suspected heparin resistance in an acute phase of sickness, where timely intervention was able to prevent a potentially fatal situation. Abbreviations: Neuroendocrine tumors (NETs), World health Organization (WHO), Radiation therapy (RT)